Xanthine oxidase activity in patients with age-related cataract associated with hypertension - Kisic,B. (2018)
Reactive oxygen species and lipid peroxidation are important factors that contribute to the development of age-related cataract. The study included 130 patients with age-related cataract, 69 of whom were diagnosed with hypertension (HT), 20 with hypertension and type 2 diabetes mellitus (DM), and 41 had no accompanying condition. The following parameters were measured in the serum of the examinees: products of lipid peroxidation malondialdehyde (MDA) and lipofuscin-like fluorophores (LLF), activity of prooxidative enzymes xanthine oxidase (XO) and myeloperoxidase (MPO), antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx), the concentration of thiol groups, and the ferric reducing activity of plasma. The activity of prooxidative enzymes XO and MPO was higher in the plasma of patients with HT (XO=9.0±1.2 U/L; MPO=77.3±8.4 U/L) and with HT and DM (XO=11.9±0.9 U/L; MPO=89.5±5.0 U/L) compared to patients with age-related cataract (XO=6.2±0.9 U/L; MPO=52.4±6.3 U/L; P<0.01). Our research has shown that patients with age-related cataract and hypertension were exposed to increased oxidative damage of biomolecules, based on the increased plasma LLF and MDA content and decreased levels of thiol groups. Oxidative changes of biomolecules in these patients were associated with increased activity of the XO, MPO, and GPx enzymes and a lower extracellular SOD activity and total ferric reductive ability of plasma.